Biliary complications adversely affect patient and graft survival after liver retransplantation. Issue 9 (18th August 2013) - Enestvedt, C. Kristian; Malik, Saloni; Reese, Peter P.; Maskin, Alexander; Yoo, Peter S.; Fayek, Sameh A.; Abt, Peter; Olthoff, Kim M.; Shaked, Abraham
<x xml:space="preserve">Abstract</x> Inferior outcomes are consistently observed for recipients of liver retransplantation (re‐LT) versus recipients of primary transplants. Few studies have examined the incidence and impact of biliary complications (BCs) on outcomes after re‐LT. The aim of this study was to compare patient and graft survival for re‐LT recipients with BCs (BC+) and re‐LT recipients without BCs (BC−). Additional aims were to determine the impact of biliary reconstruction on the incidence of BCs and to identify risk factors for BCs after re‐LT. A single‐center, retrospective analysis of all re‐LT recipients over a decade was performed. Univariate analyses were performed, and survival was compared with the log‐rank method. A multivariate Cox regression analysis was performed to determine independent predictors of death and graft failure. The BC rate was 20.9% (n = 23) for 110 re‐LT cases. The average follow‐up was 55 months. The survival rates for BC− recipients at 3 months and 1, 3, and 5 years were 95.3%, 91.7%, 85.4%, and 80.9%, respectively, whereas BC+ patients had survival rates of 64.3%, 49.7%, 34.8%, and 29.8%, respectively (P < 0.001, log‐rank). The graft survival rates at 3 months and 1, 3, and 5 years were 92.0%, 88.5%, 82.4%, and 78.0%, respectively, for the BC− group and 60.9%, 43.5%, 30.4%, and 26.1%, respectively, for the BC+ group (P < 0.001, log‐rank). BCs, a length of stay ≥ 12 days, and donor age were strongly associated with death and graft failure in a regression analysis, whereas retransplant indications other than chronic rejection and recurrent disease also affected graft failure. In conclusion, BCs significantly affected both patient and graft survival, with an increased risk of death and graft loss among BC+ recipients. Early recognition, appropriate interventions, and preventative measures for BCs are critical in the clinical management of re‐LT recipients. Liver Transpl 19:965–972, 2013. © 2013 AASLD.